Effects of Digital Storytelling Package on Students’ Motivation and Attitude to Christian Religious Studies (CRS) in Junior Secondary Schools - Adetunmbi L. Akinyemi; Jonathan Iyanuoluwa Makinde (West African Journal of Open and Flexible Learning)
This study seeks to determine the effectiveness of using a digital storytelling package on students’ motivation and attitude towards Christian Religion Studies in Junior Secondary Schools in Oyo state, Nigeria. The effect of gender was also measured. The study adopted a quasi-experimental pre-test, post-test, and control group design. The sample consisted of junior secondary school III students selected through the purposive sampling technique. The instruments used for data collection were Questionnaire on Student’ Attitude to CRS (r = 0.85), and Questionnaire on Student Motivation in CRS (r = 80). Data was analysed using Analysis of covariance and Estimated Marginal Means (EMM) at 0.05 level of significance. The findings of this study revealed that students exhibit a low level of motivation and a negative attitude towards learning C.R.S. Additionally, there was a significant effect observed from the digital storytelling package on both the motivation and attitude of students (F (2; 61) = 29.67; p = 0.49 for motivation, and F (2; 61) = 32.49; p = 0.52 for attitude). Furthermore, no significant effect of gender on students’ motivation and attitude towards C.R.S. was observed. Based on these findings, it is recommended, among other strategies, that teachers teaching C.R.S. in secondary schools should consider adopting instructional strategies like digital storytelling to enhance the motivation and attitude of students, potentially influencing their moral values significantly.